2018
DOI: 10.26603/ijspt20180882
|View full text |Cite
|
Sign up to set email alerts
|

Isokinetic Muscle Performance After Anterior Cruciate Ligament Reconstruction: A Case-Control Study

Abstract: Background and Purpose: Knee muscle strength deficits have been reported in individuals who have undergone anterior cruciate ligament reconstruction (ACLR). Isokinetic testing is a valid way to assess muscle strength. Some isokinetic variables, including the range of motion in the phases to attain a specific velocity, load range (sustained specific velocity), time to achieve deceleration, and qualitative analysis of the torque-angle velocity relationship, may contribute to understanding recovery of these indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
0
4
0
2
Order By: Relevance
“…For 0 to 6 months after ACLR, strong evidence with a large effect size (8 LR studies, homogeneous) showed that limbs with ACLR had lower quadriceps strength compared with matched control limbs (SMD, –1.42; 95% CI, –1.62 to –1.23; I 2 = 0%) ( Figure 2 ). 1 , 7 , 10 , 17 , 30 , 35 , 40 , 45 For 6 to 18 months after ACLR, strong evidence with a large effect size (7 LR studies, homogeneous) showed that ACLR limbs had lower quadriceps strength compared with matched control limbs (SMD, –0.92; 95% CI, –1.18 to –0.66; I 2 = 0%) ( Figure 2 ). 6 , 19 , 34 , 36 , 50 , 58 , 59 For >18 months after ACLR, moderate evidence (7 LR studies, heterogeneous) with a small effect size showed that ACLR limbs had lower quadriceps strength when compared with matched control limbs (SMD, –0.38; 95% CI, –0.79 to 0.03; I 2 = 76%) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For 0 to 6 months after ACLR, strong evidence with a large effect size (8 LR studies, homogeneous) showed that limbs with ACLR had lower quadriceps strength compared with matched control limbs (SMD, –1.42; 95% CI, –1.62 to –1.23; I 2 = 0%) ( Figure 2 ). 1 , 7 , 10 , 17 , 30 , 35 , 40 , 45 For 6 to 18 months after ACLR, strong evidence with a large effect size (7 LR studies, homogeneous) showed that ACLR limbs had lower quadriceps strength compared with matched control limbs (SMD, –0.92; 95% CI, –1.18 to –0.66; I 2 = 0%) ( Figure 2 ). 6 , 19 , 34 , 36 , 50 , 58 , 59 For >18 months after ACLR, moderate evidence (7 LR studies, heterogeneous) with a small effect size showed that ACLR limbs had lower quadriceps strength when compared with matched control limbs (SMD, –0.38; 95% CI, –0.79 to 0.03; I 2 = 76%) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…When the analyses were restricted to studies that reported isokinetic quadriceps strength, for 0 to 6 months after ACLR, strong evidence with a large effect size (6 LR studies, homogeneous) showed that limbs with ACLR had lower isokinetic quadriceps strength compared with matched control limbs (SMD, –1.46; 95% CI, –1.67 to –1.25; I 2 = 0%) ( Appendix Figure A3 ). 1 , 7 , 10 , 17 , 40 , 45 For the 6- to 18-month strata, strong evidence with a large effect size (6 LR studies, homogeneous) showed that ACLR limbs had lower isokinetic quadriceps strength compared with matched control limbs (SMD, –1.04; 95% CI, –1.39 to –0.70; I 2 = 35%) ( Appendix Figure A3 ). 6 , 19 , 34 , 36 , 50 , 58 For >18 months after ACLR, pooled analysis was not performed because only 3 studies were available.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the real testing was carried out. Similar procedures to the warm-up and familiarization were performed according to the study [ 31 ]. The ankle isokinetic protocol was characterized by a set of six repetitions at each velocity, performed in a simple draw, with a rest period of 90 s between sets.…”
Section: Methodsmentioning
confidence: 99%
“…Daher sind die hinteren Oberschenkelmuskeln für die dynamische Gelenkstabilität und die neuromuskuläre Kontrolle des Knies von entscheidender Bedeutung. Darüber hinaus kommt es nach der Transplantation der Patellasehne zu Kraft- und Ausdauerverlust in der Quadrizeps- und Oberschenkelmuskulatur, und dieser Zustand hält etwa ein bis vier Jahre an 7 8 . Aufgrund dieser Situation sind zu gegebener Zeit spezifischere Trainingsmethoden erforderlich, um die Kraft und Muskelausdauer der peripheren Kniemuskulatur zu verbessern 9 .…”
Section: Einführungunclassified